Analysis of the key component puff-by-puff transport in special segments and aerosol for electrical heated tobacco product - Jin, Xinyan; Meng, Decai; Fu, Lili; Zhao, Yang; Zhang, Qi; Zhang, Zhan; Yin, Xianzhong; Shen, Qinpeng; Wang, Shuang; Zhang, Yue; Wang, Le; Lei, Ping; et al. (Frontiers in Chemistry, 2024)
This study investigates the puff-by-puff release patterns of key components in Natural Smoke Cigarettes (NSCs), which are designed to deliver nicotine without combustion by reducing oxygen content, utilizing a 30second puff interval, a 2-second puff duration, and a 55mL puff volume to simulate realistic smoking conditions.By establishing models to analyze the variation of nicotine, glycerol, 1,2-propylene glycol (PG), and water in different functional sections of the cigarette under controlled smoking conditions. These sections include the tobacco, hollow, cooling, and filter sections, constituting the structure of NSCs. In addition, the model calculates the port-by-port release of the components in the flue gas aerosol and compares it with the measured value. The results showed that: The retention amount in the tobacco section showed a steep decline in the first three puffs, with an overall exponential decrease. The amounts in the other sections were consistent, increasing in the first two puffs and then stabilizing. The retention amount decreased linearly with each puff, with a similar pattern across sections.The release amount peaked at the fourth to fifth puffs and then stabilized. The retention amount in the tobacco section declined exponentially in the first three puffs. It peaked in the second to third puffs in other sections, then decreased with each subsequent puff. The retention amount in the tobacco section showed a significant decline in the first puff, stabilizing at around 4 mg. In other sections, it peaked at the first puff and then rapidly declined. These findings can inform the development of reduced-harm smoking products and contribute to a better understanding of the dynamics of smoke generation. Additionally, the study offers a reference for the puff-by-puff release stability of NSCs and the improvement of consumers' sensory quality.